2019
DOI: 10.17161/kjm.v12i3.11798
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Blunt Traumatic Splenic Injury Treated with Conservative or Operative Management

Abstract: Introduction Laparotomy, embolization, and observation are described for blunt splenic injury management. This study evaluated outcomes of blunt splenic injury management based on baseline factors, splenic injury severity, and associated injuries. Methods A nine-year retrospective review was conducted of adult patients with blunt splenic injury. Collected data included demographics, injury characteristics, treatment modality, complications, and outcomes (mechanical ventilation, days on mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Complications from SAE have been reported with a wide range of incidence (Table 2). Major complications range from 0 to 29% and minor complications range from 5% to 62% (58,66,67,79,80). A multi-institutional retrospective review of 140 patients showed an overall complication rate of 36% with a 20% major complication rate and 23% minor complication rate (67).…”
Section: Complications From Saementioning
confidence: 99%
See 1 more Smart Citation
“…Complications from SAE have been reported with a wide range of incidence (Table 2). Major complications range from 0 to 29% and minor complications range from 5% to 62% (58,66,67,79,80). A multi-institutional retrospective review of 140 patients showed an overall complication rate of 36% with a 20% major complication rate and 23% minor complication rate (67).…”
Section: Complications From Saementioning
confidence: 99%
“…A multi-institutional retrospective review of 140 patients showed an overall complication rate of 36% with a 20% major complication rate and 23% minor complication rate (67). No significant difference in overall complication rate has been demonstrated between proximal and distal embolization (66,67,79,85). Recurrent intra-abdominal bleeding was the most common major complication and occurred in 11% of patients requiring either repeat embolization or splenectomy (67).…”
Section: Complications From Saementioning
confidence: 99%
“…Overall, most patients were male (n = 58), were a median age of 26 (21-42) years old, most (n = 62) had no comorbidities, and 47 had been injured from a ski/snowboarding accident. Compared to admitted patients, significantly more females were transferred, (13/38 vs. 3/36, p = 0.007, Table 1), more had an abbreviated injury scale score (AIS) ≥ 3 (vs < 3) of the chest (31/38 vs. 7/35, p = 0.002) and had a higher injury severity score (16 (16-22) vs. 13 (9)(10)(11)(12)(13)(14)(15)(16), p = 0.008), in comparison to admitted patients.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, lower-level trauma centers with limited resources must expeditiously decide who can be immediately transferred to a higher level of care for SAE and who can be safely admitted for either surgery (exploratory laparotomy and splenectomy) or observation. Although there are a proliferation of studies examining the triage of splenic injuries [3,[6][7][8][9][10][11][12][13][14][15], there are a paucity of studies on management of patients with blunt splenic injuries in remote settings and of the few that exist, most report very small numbers and are not current [16,17]. There continues to be great variability in the processes of care for splenic injury patients, with sparse data reported across Level III or IV trauma centers.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the patients in the operative and embolization groups had similar splenic injury grades, but patients in the operative group had more severe hemoperitoneum. 15…”
Section: Complicationsmentioning
confidence: 99%